2017
DOI: 10.3389/fpls.2017.01337
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Glycerol-3-Phosphate Acyltransferase from Suaeda salsa Improves Salt Tolerance in Arabidopsis

Abstract: Glycerol-3-phosphate acyltransferase is the first acyl esterifying enzyme in phosphatidylglycerol (PG) synthesis process. In this study, we isolated and characterized the glycerol-3-phosphate acyltransferase (GPAT) gene from Suaeda salsa (S. salsa) and obtained the full length of the GPAT gene from S. salsa (SsGPAT) by 5′ and 3′ RACE. The clone contained an open reading frame (ORF) of 1167 bp nucleotides that comprised of 388 amino acid residues. Real-time PCR revealed that the mRNA accumulation of GPAT in S. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(87 citation statements)
references
References 58 publications
2
85
0
Order By: Relevance
“…Unfortunately, sequence information regarding the SsGPAT gene is not currently available, and therefore, it is unknown where this gene falls phylogenetically. The reduced level of salt tolerance was also reported for Atgpat2 and Atgpat6 mutants in the same study but the mechanism of these two GPATs’ contribution to salt tolerance has yet to be fully characterized (Sui et al, ). Moreover, though a role in stress response (chilling tolerance) has been well documented for plastidial GPAT, as previously discussed, very little is currently known regarding the function of other GPAT in this context.…”
Section: Other Plant and Algal Gpatsupporting
confidence: 55%
See 2 more Smart Citations
“…Unfortunately, sequence information regarding the SsGPAT gene is not currently available, and therefore, it is unknown where this gene falls phylogenetically. The reduced level of salt tolerance was also reported for Atgpat2 and Atgpat6 mutants in the same study but the mechanism of these two GPATs’ contribution to salt tolerance has yet to be fully characterized (Sui et al, ). Moreover, though a role in stress response (chilling tolerance) has been well documented for plastidial GPAT, as previously discussed, very little is currently known regarding the function of other GPAT in this context.…”
Section: Other Plant and Algal Gpatsupporting
confidence: 55%
“…However, unlike AtGPAT1 , both AtGPAT2 and AtGPAT3 have been found to be expressed at low levels in a rather broad range of plant tissues (including roots, seedlings, leave stem, flower, and siliques) (Beisson et al, ; Suh, Samuels, & Jetter, ; Yang et al, ; Zheng et al, ). Moreover, GPAT2 activity may be induced in some plant tissues through external stimuli such as salt stress (Sui, Tian, Wang, Wang, & Fan, ; Zheng et al, ). Intriguingly, a recent study of the rice OsGPAT3 , which is a closely related homolog of AtGPAT3 , demonstrated that in a similar manner to AtGPAT1 , this gene plays a crucial role in male fertility through its function in anther development and pollen formation (Men et al, ).…”
Section: The Role Of Mitochondrial Gpat In Pollen‐lipid Biosynthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the effects of NO in cotton, exogenous hydrogen sulfide production enhances salt tolerance by decreasing Na + content in wheat seedlings . During salt acclimation in Arabidopsis thaliana , cell wall remodeling, ethylene biosynthesis, and signaling pathways play crucial roles . K + and Ca 2+ homeostasis are also important .…”
Section: Salt Stressmentioning
confidence: 96%
“…Cilia can be typically divided into primary nonmotile cilia and motile cilia, depending on the axoneme structure. The axoneme of primary cilia is arranged in a ring of nine peripheral doublet microtubules (termed a 9 + 0 axoneme), and the axoneme of a motile cilium has two single microtubules at the center of the nine peripheral doublet ring (termed a 9 + 2 axoneme) . In addition, the peripheral doublets of motile cilia are attached by inner and outer dynein arms, which allow ciliary movement by ATP‐dependent conformational alterations.…”
Section: Structure and Function Of Airway Ciliamentioning
confidence: 99%